Análise da locomoção e estudos por imagens em porcos com sindactilia - Justolin, Pedro Luis Trevizan [UNESP] (2015)
Ten Brazilian mini pigs (Sus domesticus), from 6 to 8 months old, were divided into two groups: Group 1 - five healthy animals weighing from 10.5 to 18.5 kg and Group 2 - five animals with syndactyly weighing from 7.5 to 18.0 kg. In both groups radiographic and computed tomography studies were performed in the fore and hind limbs. Moreover, gait analysis was performed by using pressure sensing walkway. Imaging studies showed that the animals had involvement of all limbs. In particular, one limb with complex-1syndactyly and eight limbs with complex-2 syndactyly were detected in the forelimbs. In the hind limbs, four limbs with simple syndactyly, one limb with complex-1 syndactyly and five limbs with complex-2 syndactyly were observed. There were no significant differences of the kinetic and temporospatial values between groups as well as in the symmetry indices. The plantar surface of the feet and palmar surface of the hands of the clinically healthy pigs had two peak pressure plots whereas only one peak pressure plot was observed in pigs with syndactyly. In conclusion, in the evaluated population the most common type of syndactyly was complex-2 and despite of the lesions, most of data obtained using pressure sensing walkway was similar to those of normal pigs